PCOS and Role of Cumulus Gene Expression in Assessing Oocytes Quality - Sayutti, Nurainie; Abu, Muhammad Azrai; Ahmad, Mohd Faizal (Frontiers in Endocrinology, 2022)
The global infertility rate has been declining from year to year. PCOS is one of the treatable accountable causes contributing to anovulatory infertility. Nevertheless, the success rate of treatments and live-birth outcomes especially involving assisted reproductive techniques is still not very promising. There is a reduction in the development potential of oocytes and high-quality embryos in PCOS patients compared to non-PCOS patients. A critical step in IVF treatment is the assessment of oocyte and embryo competence before embryo transfer. Oocytes in metaphase II are very fragile. Repeated morphological assessment on these oocytes may directly impair the quality and affect the whole process. Identification of potential biomarkers especially in the cumulus cells oocytes complex will help to predict the outcome and may create space for improvement. This review has explored gene expression in cumulus cells with regards to oocytes quality in both normal and PCOS women. The gene expression was classified according to their physiological function such as the contribution on cumulus expansion, cumulus cells apoptosis, and glucose metabolism. Collectively, the review suggested that positive expression of HAS2, PTX3, GREM1, and VCAN may correlate with good quality oocytes and can be used as an indicator among PCOS women.